Nodular lymphocyte predominant Hodgkin lymphoma in Sweden between 2000 and 2014: an analysis of the Swedish Lymphoma Registry. (24th February 2017) - Molin, Daniel; Linderoth, Johan; Wahlin, Björn E.
Summary: Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) is an indolent CD20 + lymphoma. Its scarcity has made clinical trials difficult and there is no consensus on first‐line treatment. We conducted a population‐based study of all patients diagnosed with NLPHL in Sweden between 2000 and 2014 ( N = 158; 41 women and 117 men), focusing on clinical features, therapy and overall survival. The median female and male age was 59 and 44 years, respectively ( P = 0·002). In early‐stage disease, there was little mortality and no survival differences between therapies. In patients with advanced‐stage disease, mortality was relatively high in patients who did not receive first‐line rituximab but absent in those who did (10‐year survival, 55% vs. 100%; P = 0·033); there were no imbalances of prognostic factors between those two groups. In advanced stages, first‐line rituximab use increased markedly between 2000–2004 and 2005–2014 (7% vs. 67%; P < 0·00005), as did 10‐year survival, 53% vs. 72% (multivariate P = 0·027). Although all patients were diagnosed in the 2000s, this is the longest‐followed (and largest) population‐based cohort. We report a hitherto unreported 15‐year median age difference between sexes, increasing rituximab use and improved survival.